Flood pattern changes in the rivers of the Baltic countries - Sarauskiene, Diana; Kriauciuniene, Jurate; Reihan, Alvina; Klavins, Maris (Journal of Environmental Engineering and Landscape Management, 2015)
Estimation of both the frequency and variation of spring floods is a key issue for the assessment and management of flood risks. Changes in river floods in Estonia, Latvia and Lithuania have been investigated in few national studies. However, there are no studies of the changes of flood patterns by using a common methodology for the rivers of this region. In this study flood pattern changes in the rivers of the Baltic countries were estimated applying trend and frequency analysis for the periods of 1922–2010, 1922–1960, 1961–2010 and 1991–2010, i.e. for the whole spring flood data sets, periods before and after 1960 (this year was considered as the beginning of the remarkable climate change), as well as for the two past decades. A comparative study of five probability distributions was performed in order to estimate which distribution at best represents statistical characteristics of the flood data. The results showed that maximum discharges of spring floods decreased over the whole studied period. Only some insignificant positive trends of maximum discharges were found in the last time period in continental and transitional rivers. Generalized extreme value distribution provided the best approximation to the maximum discharge data series of the rivers of Baltic countries for the whole observation period.First published online: 08 Jul 2014